Pharmacokinetics and anti‐inflammatory effects of flunixin meglumine as a sole agent and in combination with phenylbutazone in exercised Thoroughbred horses. (17th April 2020) - Knych, Heather K.; Arthur, Rick M.; McKemie, Daniel S.; Baden, Russell W.; Seminoff, Kelsey; Kass, Philip H.
Abstract: Background: Flunixin meglumine (FM) and phenylbutazone (PBZ) are potent anti‐inflammatory agents and as such their potential to mask injuries that would otherwise keep a horse from training or racing is concerning. A common practice in racetrack medicine in the USA is to administer the two drugs within close proximity (24 hours apart) of each other, raising the concern of pharmacokinetic interactions and enhanced anti‐inflammatory effects. Objectives: Describe the pharmacokinetics and effects of PBZ on the clearance of FM when administered in close proximity as well as effects on inflammatory mediators. Study design: Two‐way randomised balanced crossover experiment. Methods: Twelve Thoroughbred exercised horses received 500 mg FM IV alone or in combination with 2 g of IV PBZ 24 hours later. Blood and urine samples were collected prior to and for up to 120 hours post‐drug administration. Whole blood samples were collected at various times and challenged with lipopolysaccharide or calcium ionophore to induce ex vivo synthesis of eicosanoids. Concentrations of FM, PBZ and eicosanoids were measured using LC‐MS/MS and noncompartmental pharmacokinetic analysis performed on concentration data. Results: Flunixin meglumine clearance was significantly increased when horses received PBZ 24 hours post‐administration ( P = .03). No other differences in pharmacokinetic parameters were noted between groups. Thromboxane B2 was significantly suppressed, relative to baseline for 96 hours post‐FM administration. Subsequent administration of PBZ prolonged the suppression. Prostaglandin E2 was decreased for 24 hours following administration of FM with subsequent administration of PBZ prolonging the suppression until 120 hours. PGF2alpha concentrations were decreased for up to 168 hours post‐FM administration. FM administration significantly decreased 15‐HETE. Main limitations: Small sample size and lack of a phenylbutazone‐only treatment group. Conclusions: Administration of PBZ post‐FM administration increased FM clearance. The anti‐inflammatory effects of FM appear to be prolonged when PBZ is administered 24 hours post‐administration.